From Biomphalaria glabrata to Drosophila melanogaster and Anopheles gambiae: the diversity and role of FREPs and Dscams in immune response - Li, Hongyu; Zhao, Qingzhi; Xu, Jialu; Li, Xianwei; Chen, Xintong; Zhang, Yijie; Li, Hairun; Zhu, Yunhuan; Liu, Mingcheng; Zhao, Ling; Hua, Dingji; Zhang, Xiaofen; et al. (Frontiers in Immunology, 2025)
Fibrinogen-related proteins (FREPs) and Down syndrome cell adhesion molecules (Dscams) are important immune-related molecules in invertebrates. Although they are found in different taxonomic groups and possess unique functions, both exhibit high diversity and adaptability. FREPs are characterized by their fibrinogen-related domains and have been primarily studied in mollusks, such as Biomphalaria glabrata. Through mechanisms of diversity generation, such as gene conversion and point mutations, BgFREP plays a critical role in the host’s defense against parasites. Dscams are immunoglobulin-like transmembrane proteins, mainly studied in arthropods, such as Drosophila melanogaster and Anopheles gambiae. Through alternative splicing, Dscams generate multiple isoforms that participate in pathogen recognition and the precise wiring of neural circuits. In D. melanogaster, DmDscam plays a role not only in neuronal self-recognition but also in pathogen recognition. In A. gambiae, AgDscam defends against parasite infections, by binding to pathogens and mediating phagocytosis. This paper highlights the key roles of FREPs and Dscams in the immunity of two major invertebrate groups—mollusks and arthropods—and summarizes the main advancements in current research. These studies not only deepen the understanding of invertebrate immune mechanisms but also lay a solid foundation for future exploration of their potential applications in the biomedical field.